SWOT – аналіз перспектив розвитку лікувально-оздоровчого туризму (на прикладі санаторію „Брусниця”) - Костащук, Володимир, Іванович; Костащук, Марина, Іванівна; Лакуста, Василь, Васильович (Чернівецький національний університет імені Юрія Федьковича, 2017)
В статті викладено основні теоретико-методичні аспекти проведення SWOT-аналізу в туристично-рекреаційному комплексі. Наприкладі Брусницького санаторію проведено локальний SWOT-аналіз слабких і сильних чинників перспективного розвитку даного суб’єкту рекреаційно-туристичного комплексу Чернівецької області. На основі проведеного дослідження обгрунтовано заходи які необхідно вжити як органам влади так зацікавленим підприємцям для прискореного розвитку санаторію. SWOT analysis is a process of establishing links between the features, threats, strengths (advantages), weaknesses that are most characteristic of an enterprise, the results of which can be used for the future formulation and selection of enterprise strategies. The economic crisis and the excessive influence of society on the natural environment of Ukraine at a rapid rate have increased morbidity and decreased indicators of natural growth rate of the population. Therefore, the problems of health improvement, treatment, and health care of the population are extremely relevant at present. Thanks to unique mineral waters, which are not even analogous in Europe, and favorable landscape and climatic conditions the region can enter the international market for recreational and tourist services. It is proposed to conduct a SWOT analysis of the Brusnytsia Balneology Sanatorium in order to determine the potential of tourism in Brusnytsia recreational and tourist center and the priority directions of its development and strategies of activity. Brusnytsia Mineral Water Mineral Deposit is the most valuable for recreational and tourist development of health-improving tourism in the region. It is rated by the highest categories. There are three groups of mineral water here. A great and unique potential of balneological resources is concentrated in Brusnytsia, and it is used insufficiently. Thanks for the mineral water with a unique chemical composition, the medicinal efficiency of water procedures is 94.8 percent. This is one of the highest rates of recovery across the entire territory of Ukraine. A comprehensive study of the situation around the sanatorium is impossible without the use of classical techniques and tools. We conduct a SWOT-analysis in order to identify the strengths and weaknesses, market threats and opportunities. In the course of SWOT-analysis, the analysis of the enterprise under investigation is carried out on the strengths and weaknesses of the internal and external environment. For this health-improving institution the strengths and weaknesses, threats and opportunities characterize the signs for the development of the enterprise. To assess the factor of the internal environment, we use a 3-point system of evaluation. Accordingly, 3 points indicate a strong side, and 1 point indicates a weak side. Once the internal environment has been analyzed and the list of strengths and weaknesses has been compiled, it is necessary to establish link lines, namely, to establish paired combinations between them. A special matrix has been created to identify the links. Based on the developed SWOT-matrix we identify and analyze in each matrix field all paired combinations of strengths, weaknesses, opportunities and threats in the external environment, where we need to focus on the assessment of these factors. This allows us to create a list of weaknesses and strengths, as well as the threats and opportunities of this health-improving institution. The final matrix allows us to identify all combinations of strengths, opportunities, and weaknesses and threats. Therefore, in identifying directions for the development of a sanatorium in this field, one should look at the maximum indicators (assessments) of the opportunities and weaknesses of the enterprises. According to the results of the conducted studies, we can note that the sanatorium is experiencing a severe crisis due to such factors as: weak marketing activity, narrow range of services, poor material and technical base, low level of development of tourist infrastructure, unsatisfactory condition of highways and other negative factors that can cause many threats to the future functioning of the sanatorium. The effective solution of these problems will allow the Brusnytsia sanatorium to enter the world market of recreational services.
SWOT analysis of the prospects for the development of health-improving tourism (on the example of the sanatorium Brusnytsia)
Keywords: SWOT-анализ; Брусницкий санаторий; рекреационно-туристический центр; стратегическое планирован. SWOT-analysis; Brusnytsia sanatorium, recreational and tourist center; strategic planning. ие.